The Contextual Relation between Ideology and Political Violence: Khmer Rouge - Ezikoglu, Caglar; Karabulut, Andac; Merdan, Ali Samir (Southeast Asia Development Research, 2025)
During the Cold War era in the world, the ideological approaches of the East and the West driven by the bipolar system directly influenced the state systems. The Soviet Union’s communist system, in particular, made a significant impact in Asia, notably due to the dominant role of the People’s Republic of China. With the critical role of China, the communist regime stood out as a distinctive ideology in the Asian territories. The exploitation efforts by imperial powers such as the United States, France and the United Kingdom in Asia led to torture and oppression, resulting in the repugnance and hatred of people. This repugnance not only sparked a revolutionary movement in Vietnam but also gave rise to terrorist activities in the Cambodian territories. Founded during the Pol Pot regime, the Khmer Rouge violent regime led to a brutal mass murder of millions of people especially in Cambodia under the Communist regime. The present study focuses on the massacre of the Vietnamese people by the Communist Pol Pot violent regime under the communist regime. Thus, the contextual relationship between ideology and political violence is tried to be proved with the data obtained from this case study, elite interviews and other secondary sources.